PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI HOTEL INNA GRAND BALI BEACH - Ayu Sekar, Ni Komang; Kartika Dewi, A.A Sagung; Ardana, Komang (E-Jurnal Manajemen, 2017)
Organizational Citizenship Behavior (OCB) is a person's behavior is voluntary, includes the behavior of helping others, volunteering for extra duties, adherence to the rules and procedures in the workplace. The purpose of this study is to determine the effect of transformational leadership and communication on OCB. This research was conducted at the Inna Grand Bali Beach. The number of samples used in this study as many as 80 employees with proportionate stratified random sampling technique. Data analysis technique used is multiple linear regression analysis. Results of the analysis showed that transformational leadership and significant positive effect on OCB at Inna Grand Bali Beach and communication are also positive and significant impact on OCB at Inna Gr Bali Beach. A leader and communication have an important role to berjalanya a company because if a company does not have a leader and good communication, the destination desired by the company can not be achieved with good.
Keywords: transformational leadership, communication, organizational citizenship behavior